Virtual Terroir and the Premium Coffee Experience - Barbosa Escobar, Francisco; Petit, Olivia; Velasco, Carlos (Frontiers in Psychology, 2021)
With its origin-centric value proposition, the specialty coffee industry seeks to educate consumers about the value of the origin of coffee and how the relationship with farmers ensures quality and makes coffee a premium product. While the industry has widely used stories and visual cues to communicate this added value, research studying whether and how these efforts influence consumers’ experiences is scarce. Through three experiments, we explored the effect of images that evoke the terroir of coffee on the perception of premiumness. Our results revealed that online images that resembled the broad origin of coffee (i.e., a farm) could influence premiumness expectations of coffee (Experiment 1). Similarly, a virtual reality environment that depicted this broad origin (vs. a control but not a city atmosphere) could enhance the perception of coffee premiumness for non-expert consumers (Experiment 2) and the enjoyment of the experience for coffee professionals (Experiment 3). Importantly, we found that congruence between the coffee and the VR atmospheres mediated how much non-experts enjoyed the experience (Experiment 2). VR atmospheres also influenced expectations of sweetness and acidity for non-experts (Experiment 2). These findings serve as a steppingstone for further exploration of the effects of congruence between visual cues and product/brand attributes on premiumness expectations and perception, and more generally on consumer experience. From a practical standpoint, this study provides insights into key aspects for the development of immersive virtual product experiences.